Influence of religiosity/spirituality on informal caregivers of children with leukemia - Farinha, Francely Tineli (2023)
Faced with diagnosis and treatment of serious illness in children, including oncology, parents, especially mothers, tend to fully assume the demands of care and, consequently, must develop situational coping strategies. In this regard, this descriptive and cross-sectional study sought to identify the use of religious/spiritual coping by informal caregivers of children with acute lymphoid leukemia via the Brief Religious/Spiritual Coping (SRCOPE) scale. A total of 30 informal caregivers participated in the study, presenting high religious/spiritual coping (mean=3.90; SD=0.34) regarding positive methods (mean=3.67; SD=0.48). Finally, results show that mothers use religious/spiritual coping deal with the imposed demands for care, linked to the child’s health condition. This reinforces the possibility of using spirituality and or religiosity as indicators of physical and mental well-being, since the quality of care is closely related to the caregivers’ health.